Serum Creatinine Monitoring After Acute Kidney Injury in the PICU*. Issue 4 (21st January 2021) - Robinson, Cal; Benisty, Kelly; Cockovski, Vedran; Joffe, Ari R.; Garros, Daniel; Riglea, Teodora; Pizzi, Michael; Palijan, Ana; Chanchlani, Rahul; Morgan, Catherine; Zappitelli, Michael
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: It is unknown whether children with acute kidney injury during PICU admission have kidney function monitored after discharge. Objectives: 1) describe postdischarge serum creatinine monitoring after PICU acute kidney injury and 2) determine factors associated with postdischarge serum creatinine monitoring. Design: Secondary analysis of longitudinal cohort study data. Setting: Two PICUs in Montreal and Edmonton, Canada. Patients: Children (0–18 yr old) surviving PICU admission greater than or equal to 2 days from 2005 to 2011. Exclusions: postcardiac surgery and prior kidney disease. Exposure: acute kidney injury by Kidney Disease: Improving Global Outcomes serum creatinine definition. Interventions: None. Measurements: Primary outcome: postdischarge serum creatinine measured by 90 days, 1 year, and 5–7 years. Secondary outcomes: Healthcare events and nephrology follow-up. ANALYSIS: Proportions with outcomes; logistic regression to evaluate factors associated with the primary outcome. Kaplan-Meier analysis of time to serum creatinine measurement and healthcare events. Main Results: Of n = 277, 69 (25%) had acute kidney injury; 29/69 (42%), 34/69 (49%), and 51/69 (74%) had serum creatinine measured by 90 days, 1 year, and 5–7 year postdischarge, respectively. Acute kidney injury survivors were more likely to have serum creatinine measured versus nonacute kidney injury survivors at all time points ( p ≤ 0.01). Factors associated with 90-day serum creatinine measurement were inpatient nephrology consultation (unadjusted odds ratio [95% CI], 14.9 [1.7–127.0]), stage 2–3 acute kidney injury (adjusted odds ratio, 3.4 [1.1–10.2]), and oncologic admission diagnosis (adjusted odds ratio, 10.0 [1.1–93.5]). A higher proportion of acute kidney injury versus nonacute kidney injury survivors were readmitted by 90 days (25 [36%] vs 44 [21%]; p = 0.01) and 1 year (33 [38%] vs 70 [34%]; p = 0.04). Of 24 acute kidney injury survivors diagnosed with chronic kidney disease or hypertension at 5–7 year follow-up, 16 (67%) had serum creatinine measurement and three (13%) had nephrology follow-up postdischarge. Conclusions: Half of PICU acute kidney injury survivors have serum creatinine measured within 1-year postdischarge and follow-up is suboptimal for children developing long-term kidney sequelae. Knowledge translation strategies should emphasize the importance of serum creatinine monitoring after childhood acute kidney injury.